2013
DOI: 10.1002/mrm.24826
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive tumor hypoxia measurement using magnetic resonance imaging in murine U87 glioma xenografts and in patients with glioblastoma

Abstract: These data support further investigation of T1 -weighted OE-MRI to identify regional tumor hypoxia. The quantification of AUCOE has translational potential as a clinical biomarker of hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 45 publications
6
74
1
Order By: Relevance
“…Here, O'Connor found linear correlations between pimonidazole binding and~R 1 . This type of correlation has also been observed in a brain tumor model (36). O'Connor also demonstrated that correction for perfusion may be necessary for tumors that exhibit extensive necrosis.…”
Section: Imaging Of Hypoxia Is the Solution For Selecting Patients Fosupporting
confidence: 53%
“…Here, O'Connor found linear correlations between pimonidazole binding and~R 1 . This type of correlation has also been observed in a brain tumor model (36). O'Connor also demonstrated that correction for perfusion may be necessary for tumors that exhibit extensive necrosis.…”
Section: Imaging Of Hypoxia Is the Solution For Selecting Patients Fosupporting
confidence: 53%
“…Optical imaging techniques are capable of measuring oxygenation, but are severely limited in their penetration depth and spatial resolution due to the dominance of ballistic photon scattering [17]. Blood Oxygenation Level Dependent contrast (BOLD) MRI and oxygen-enhanced (OE) MRI are the only clinical imaging modalities capable of assessing volumetric tumour oxygenation [1820]. However, these techniques are limited by their cost and accessibility which renders them impractical for assessing the early changes in oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…Several preliminary studies have already shown the use of hyperoxic gas challenge to stimulate BOLD and/or TOLD MRI signal responses in tumors at distinct disease sites (breast [56, 57], cervix [49, 58, 59], brain [38, 60], prostate [61], and liver [62]). Breathing oxygen is particularly appropriate, since this is standard intervention in emergency medicine and thus it is quite straightforward to gain IRB approval.…”
Section: Discussionmentioning
confidence: 99%